2006
DOI: 10.1051/kmae:2006004
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Use by Native and Stocked Trout (Salmo Trutta L.) in Two Northeast Streams, Portugal

Abstract: Habitat use by stocked and native brown trout (Salmo trutta L.) was assessed in two headwater streams of North-eastern Portugal. Underwater observations were made during the summer season in three successive years to evaluate the effect of supplemental trout stocking. Multivariate analysis techniques applied to data sets on microhabitat use were exploited to identify the focal elevation (distance of fish from the bottom), total depth and cover as the variables that contribute most to the discrimination between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 45 publications
2
18
1
Order By: Relevance
“…These adverse environmental conditions make pools and visually isolated areas increasingly preferred as trout age, the selection of protected areas at river margins increasing with growing river width, and younger individuals selecting boulder sheltered positions. This pattern matches with observations from other southern brown trout populations (Vismara et al, 2001;Teixeira et al, 2006), although not with northern populations where adult trout select pool habitats but avoid river margins, and younger individuals prefer instream vegetation at river margins over boulder sheltered positions (e.g. Greenberg et al, 1996;Mäki-Petäys et al, 1997;Heggenes, 2002).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…These adverse environmental conditions make pools and visually isolated areas increasingly preferred as trout age, the selection of protected areas at river margins increasing with growing river width, and younger individuals selecting boulder sheltered positions. This pattern matches with observations from other southern brown trout populations (Vismara et al, 2001;Teixeira et al, 2006), although not with northern populations where adult trout select pool habitats but avoid river margins, and younger individuals prefer instream vegetation at river margins over boulder sheltered positions (e.g. Greenberg et al, 1996;Mäki-Petäys et al, 1997;Heggenes, 2002).…”
Section: Discussionsupporting
confidence: 86%
“…Greenberg et al, 1996;Mäki-Petäys et al, 1997;Roussel and Bardonnet, 1997;Teixeira et al, 2006). Despite physical habitat is the major determinant of spatial variations in the abundance and distribution of most salmonid populations , the distribution of younger individuals at a reach scale is affected by older fish through intercohort competition or predation (Bult et al, 1999;Vehanen et al, 1999;Nordwall et al, 2001;Vik et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also confirmed previous observations following distinct methodologies (e.g. snorkelling, electrofishing), which detected, just one month after, a low proportion of stocked brown trout in the stream segment where they had been released (Cortes et al, 1996;Teixeira et al, 2006). The potential negative impacts of stocking on wild population seemed to be limited in time and space and were demonstrated by the monitoring of fish movement (e.g.…”
Section: Resultssupporting
confidence: 91%
“…A few studies have observed that the diets of large trout have higher proportions of terrestrial invertebrates than the diets of small fish and thus demonstrate an ontogenetic shift in diets (P. Gustafsson, unpublished data; Montori et al 2006;Teixeira et al 2006;Dineen et al 2007a;Er} os et al 2010). A few studies have observed that the diets of large trout have higher proportions of terrestrial invertebrates than the diets of small fish and thus demonstrate an ontogenetic shift in diets (P. Gustafsson, unpublished data; Montori et al 2006;Teixeira et al 2006;Dineen et al 2007a;Er} os et al 2010).…”
Section: Introductionmentioning
confidence: 99%